(untitled) (Bangladesh Journal of Zoology, 2019)
Spiders are one of the important predatory arthropods that comprise the largest order Araneae of the class Arachnida. In Bangladesh, very few contributions are available on the taxonomic study on these arachnids. The present paper contains an updated checklist of the spider fauna of Bangladesh based on the published records of different workers and the identified collections of the recent studies by the author. It includes a total of 334 species of spiders belong to the infraorders Mygalomorphae and Araneomorphae under 21 families and 100 genera. A brief diagnosis of different families and their domination together with the distribution throughout the country are provided herewith. Bangladesh J. Zool. 47(2): 185-227, 2019